2017
DOI: 10.1038/s41598-017-04910-3
|View full text |Cite
|
Sign up to set email alerts
|

Perchlorates on Mars enhance the bacteriocidal effects of UV light

Abstract: Perchlorates have been identified on the surface of Mars. This has prompted speculation of what their influence would be on habitability. We show that when irradiated with a simulated Martian UV flux, perchlorates become bacteriocidal. At concentrations associated with Martian surface regolith, vegetative cells of Bacillus subtilis in Martian analogue environments lost viability within minutes. Two other components of the Martian surface, iron oxides and hydrogen peroxide, act in synergy with irradiated perchl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 31 publications
2
77
1
2
Order By: Relevance
“…Thus, some studies have positive implications showing these minerals as possible electron acceptors by microorganisms capable to provide energy for growth or as powerful antioxidants protecting plants against Mars' harsh environmental stresses and boost the rate of decomposition of organic matter (Bohle et al 2016). On the contrary, other studies show the Martian salts as a detrimental condition for life survival (Wadsworth & Cockell 2017). The presence of different living beings in extreme salt condition on Earth such as the halophilic organisms encourage the options to generate future crops and better understand the mechanisms of survival in these conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, some studies have positive implications showing these minerals as possible electron acceptors by microorganisms capable to provide energy for growth or as powerful antioxidants protecting plants against Mars' harsh environmental stresses and boost the rate of decomposition of organic matter (Bohle et al 2016). On the contrary, other studies show the Martian salts as a detrimental condition for life survival (Wadsworth & Cockell 2017). The presence of different living beings in extreme salt condition on Earth such as the halophilic organisms encourage the options to generate future crops and better understand the mechanisms of survival in these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Martian regolith has high presence of different types of salts and evaporitic minerals i.e. formed by the evaporation from bodies of water (Vaniman et al 2004;Ewing et al 2006) and they have been detected on Mars both in situ and remotely by different monitoring instruments (Wadsworth & Cockell 2017). The controversy about their effects on the habitability of that planet is still under research.…”
Section: Discussionmentioning
confidence: 99%
“…If carried, for instance, by winds at 5 m$s -1 (Gomez-Elvira et al, 2014) with the average flux mentioned above, they could travel more than 100 km without dying. However, other factors found on Mars need to be taken into account so as to reduce the planetary protection risk, such as the presence of perchlorates that have been shown to be highly damaging to life (Wadsworth and Cockell, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Many of these oxidants are known to be destructive to organic molecules and may contribute to the paucity of organics so far detected on Mars. One recent study has also shown that the presence of perchlorate and hydrogen peroxide can substantially increase the rate of cell death over and above the rate caused by UV radiation alone (Wadsworth & Cockell, 2017). One uncertainty that remains is the depth to which these reactions take place in the subsurface.…”
Section: Full Commentarymentioning
confidence: 99%